Determinants of technology transfer through CDM: The case of China - Matthias Weitzel; Wan-Hsin Liu; Andrea Vaona (Kiel Institute for the World Economy (IfW), 2013)
Technology transfer (TT) is not mandatory for Clean Development Mechanism (CDM) projects, yet proponents of CDM argue that TT in CDM can bring new technologies to developing countries and thus not only reduce emissions but also foster development. We review the quantitative literature on determinants of TT in CDM and estimate determinants for CDM projects in China. China is by far the largest host country of CDM projects and it is therefore crucial to understand the factors that drive TT there. We focus on heterogeneity within a single country and results can thus be linked to specific policies of the country for better interpretation. Our probit estimations confirm results of international cross-country studies, indicating that larger projects and more advanced technologies are more likely to involve TT. In addition, we find evidence that agglomeration effects are more pronounced on the province level rather than larger regions. We also find a positive effect of FDI on TT and a complementary role of academic R&D engagement to TT.
Keywords: Q33; Q55; Q58; 330; Clean Development Mechanism; Technology Transfer; R&D; Agglomeration; China